Codesigning with communities to support rural water management in Uganda. Issue 2 (3rd April 2017) - Ssozi-Mugarura, Fiona; Blake, Edwin; Rivett, Ulrike
Abstract: The use of information and communication technologies (ICTs) in developing regions has gained momentum due to their increasing affordability, particularly in rural areas where other ICT infrastructures for information management are often non-existent. Giving potential technology users, the opportunity to actively engage and contribute to the design of an artefact increases adoption and sustainable use. In this paper, we illustrate our application of community-based codesign (CBCD) that led to the development of an ICT intervention to support water management in three rural communities in Uganda. The community-based system helps water managers to track water users, payments and expenditures in a bid to improve transparency, accountability and trust. We present research learnings of the method and how engagement with rural communities can be improved through the use of intermediaries and paying more attention to community values as well as exercising ethics of reciprocity in community-based ICT initiatives.